EKSPERIMEN SAINS ANAK USIA 5-6 TAHUN DI TK AISYIYAH 5 RAWALO MELALUI PERMAINAN RAINBOW WALKING WATER (AIR PELANGI BERJALAN) - Tatik Ariyati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2021)
This research is motivated by the creativity and innovation of teachers in making APE which is indispensable in developing children's science skills in schools resulting in less varied learning methods so that children are unable to construct their own knowledge of science and other knowledge. The purpose of this research is to find out how the experimental experiment through the rainbow water game runs in developing the scientific abilities of children aged 5-6 years. This research uses descriptive research with a qualitative approach. This research was conducted at TK Aisyiyah 5 Rawalo. The results of this study develop the development of children's scientific abilities and can also develop six aspects of child development, namely cognitive, language, emotional, moral and religious development, physical-motor and art.